Human or machine driving? Comparing autonomous with traditional vehicles value curves and motives to use a car. (14th April 2020) - Antonialli, Fabio; Cavazza, Bruna Habib; Gandia, Rodrigo Marçal; Nicolaï, Isabelle; Neto, Arthur De Miranda; Sugano, Joel Yutaka; Zambalde, André Luiz
This study aims at drawing new value curves for Autonomous Vehicles (AVs) over Traditional Vehicles when considering AVs as a Product-Service System (PSS) as well as discussing the main reasons to use an AV over a traditional car. Data were collected based on secondary (academic and grey literature) and validated with AVs experts on France, Belgium, and Brazil. The results show the arrival of AVs would include different ownership forms; free time for users (no driving required); 'infotainment'; social integration of elders and handicapped people. We realise that AVs have in their business model several attributes that fit them into a new market perspective compared to the current mobility scenario. Also, we observed that as automation levels increase, machine driving components of the vehicle also increase. As conclusions, the reasons to use a car are likely to change with a decrease in symbolic and affective attributes and increase instrumental ones.